Enhancing Learning Outcomes in Kasti through the Implementation of Group Learning Method among Fifth-Grade Students at SD Negeri 064011 Medan - Dawolo, Mediso; Sari, Liliana Puspa (Educational Sciences Journal, 2025)
This empirical classroom action research aimed to improve students’ learning outcomes in the traditional sport of kasti through the application of the group learning method among fifth-grade students at SD Negeri 064011 Medan during the 2022/2023 academic year. The study was motivated by the low initial mastery of kasti skills, where only 11.5% of the students achieved the Minimum Mastery Criteria (KKM) score of 70. The research adopted the Kemmis and Taggart Spiral Model comprising two cycles, each involving stages of planning, action, observation, and reflection. The assessment rubric focused on three psychomotor components hitting, throwing, and catching techniques. Data were collected from 26 students using performance-based evaluation instruments. Findings demonstrated significant improvement across the two cycles. The average score increased from 43 in the pre-test (11.5% mastery) to 63 in Cycle I (34.6% mastery), and finally to 80 in Cycle II (80.8% mastery), surpassing the class mastery criterion of 80%. These results confirm that the group learning method effectively enhances students’ active participation, cooperation, and psychomotor skills in performing kasti techniques. The study concludes that cooperative group-based instruction fosters both cognitive understanding and motor performance in physical education learning contexts. Therefore, this method is recommended for primary-level physical education to enhance engagement and skill acquisition in team-based traditional games such as kasti.